PROTAC technology for the treatment of Alzheimer's disease: advances and perspectives - Hiroyuki Inuzuka; Jing Liu; Wenyi Wei; Abdol-Hossein Rezaeian (Compuscript Ltd, 2022)
Neurodegenerative diseases are characterized by the progression of neuronal degeneration, resulting in dysfunction of cognition and mobility. Many neurodegenerative diseases are due to proteinopathies arising from unusual protein accumulation and aggregation. The aggregation of misfolded proteins, such as β-amyloid, α-synuclein, tau, and polyglutamates, is a hallmark of Alzheimer's disease (AD). These aggregated proteins are undruggable targets and usually do not respond to conventional small-molecule agents. Therefore, developing novel technologies and strategies for decreasing the levels of protein aggregates is critical for the treatment of AD. Recently, the emerging proteolysis targeting chimera (PROTAC) technology has been considered for artificial, selective degradation of aberrant target proteins. These engineered bifunctional molecules engage target proteins, which are then degraded either by the cellular degradation machinery via the ubiquitin-proteasome system or through the autophagy-lysosome degradation pathway. Although PROTAC technology is preferable to oligonucleotides and antibodies for the treatment of neurodegenerative diseases, many limitations, such as their pharmacokinetic properties, tissue distribution, and cell permeability, must be addressed. Herein, we review recent advances in PROTAC technology, as well as PROTACs' limitations, for the pharmaceutical targeting of aberrant proteins involved in AD. We also review the therapeutic potential of dysregulated signaling, such as the PI3K/AKT/mTOR axis, for the management of AD.